2007
DOI: 10.1074/jbc.m701639200
|View full text |Cite|
|
Sign up to set email alerts
|

Ing1 Mediates p53 Accumulation and Chromatin Modification in Response to Oncogenic Stress

Abstract: ING proteins are putative tumor suppressor proteins linked to the p53 pathway and to the chromatin modification machinery. Here we have analyzed the role of the products of the murine Ing1 locus in cellular tumor-protective responses, using mouse primary fibroblasts where the Ing1 locus has been inactivated by the integration of a ␤geo cassette. We show that Ing1-deficient mouse embryonic fibroblasts display a defective senescence-like antiproliferative response against oncogenic Ras, affecting several senesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 41 publications
3
21
1
Order By: Relevance
“…This finding indicates a predominant role for Ing1 as a transcriptional repressor, in agreement with previous biochemical studies (16,18). As an internal validation of the experiment, we found that the signal for the Ing1 probe was reduced ∼10-fold in the Ing1-mutant fibroblasts (Ing1-mutant/wildtype ratio, 0.11; P = 0.0004), consistent with our previous characterization of the expression of the Ing1 locus in this cell type (24). In addition, we found that the expression of the other Ing loci is not significantly altered in Ing1-mutant cells, with the possible exception of Ing5 (Supplementary Table S1).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This finding indicates a predominant role for Ing1 as a transcriptional repressor, in agreement with previous biochemical studies (16,18). As an internal validation of the experiment, we found that the signal for the Ing1 probe was reduced ∼10-fold in the Ing1-mutant fibroblasts (Ing1-mutant/wildtype ratio, 0.11; P = 0.0004), consistent with our previous characterization of the expression of the Ing1 locus in this cell type (24). In addition, we found that the expression of the other Ing loci is not significantly altered in Ing1-mutant cells, with the possible exception of Ing5 (Supplementary Table S1).…”
Section: Resultssupporting
confidence: 80%
“…The Ing1-deficient MEFs we have used in this study display a dramatic reduction (>90%) in the expression of all the transcripts of the locus, as a consequence of the insertion of a BetaGeo genetrap cassette. The levels of the p33ING1 protein (the only ING1 peptide detectable in MEFs) are also reduced to the same extent (24). Of the 37,898 probes, representing >30,000 genes, present in the array, we found a significantly differential expression associated to Ing1 status (at least 2-fold change, see Materials and Methods) for 466 of them (∼1.2% of the total).…”
Section: Resultsmentioning
confidence: 84%
“…Consistent with this idea and our current data, it was recently reported that deletion of the Ing1 locus from murine cells impairs Ras-induced senescence (Abad et al, 2007). Hints as to how INGl, and the INGla splice isoform in particular, contribute to establishment of a senescent state are provided by the ability of INGla to repress expression of some genes such as PCNA which is required for growth while inducing others such as the pl6 and pRb which are associated with the induction of senescence, upon ectopic expression.…”
Section: Discussionsupporting
confidence: 82%
“…Neuronal gene expression, like other transcriptional processes, is modulated by a dynamic process of chromatin modifications (3)(4)(5). According to the histone code hypothesis, different modifications of histones at a particular promoter region, alone or in combination, define a specific epigenetic state that balances between gene activation and gene silencing (6,7). Although there are exceptions, histone hyperacetylation at promoters generally indicates an increase in gene activity, whereas hypoacetylation usually marks a decrease in activity (8).…”
mentioning
confidence: 99%